A Physical Abuse Case - Açik, Yasemin; Deveci, S. Erhan; Yildirim, Alpagan Mustafa; Okur, M. Ihsan (My University, 2003)
Child abuse is an important, widespread public health problem, it has different dimentions and severity, and it can cause child death. Wrong ennouncement, insufficient evidence, different culturel and traditional conditions cause the hidden of more abuse cases. In this study, a girl aged five years old who is burned by boiling water by her father is presented. She had two-three degree burn on her back, hip, inguinal and perineal zone, right dorsal hand, totaly 25%. Case's story, the result of physical examination, characteristics of lesions show physical abuse. Abuse is especially directed towards to repeat, in repeated situations death rate can be more. This presented case is important for showing the dimension of child abuse once again. Every child came with trauma story must be investigated about the probability of child abuse.
Bir Fiziksel İstismar Olgusu
Keywords: Child abuse; Physical abuse; Trauma